Optimizing nitrogen removal in advanced wastewater treatment using biological aerated filters - Li, Juan; Niu, Ziru; Li, Lei; Zhou, Shuting (Frontiers in Bioengineering and Biotechnology, 2024)
Reducing total nitrogen (TN) presents a significant challenge for numerous wastewater treatment facilities. In order to address this issue, the current study employed a biological aerated filter for the treatment of wastewater containing low nitrogen concentrations. Both lab-scale and pilot-scale biofilters were constructed to investigate the denitrification performance and maximum denitrification load. The findings indicated that the anaerobic denitrification process of established biofilm adhered to pseudo-first-order kinetics. The results of batch testing and continuous-flow experiments confirmed that the minimum hydraulic retention time (HRT) required for mature biofilm was determined to be 0.5 h. The optimal operating parameters were found to be as follows: influent NO3−-N concentration of 25 mg/L, HRT of 0.5 h, resulting in effluent TN levels below 1 mg/L. Under these conditions, the denitrifying load for the lab-scale I-BAF system was calculated to be 1.26 kg (TN)/(m3·d). Furthermore, it was observed that the maximum denitrifying load could reach 2.2 kg (TN)/(m3·d) when the influent NO3−-N concentration was increased to 50 mg/L while maintaining an HRT of 0.5 h. For the mature biofilter, the appropriate HRT ranged from 2 h to 0.5 h. Microbial diversity analysis revealed that the genus Enterobacter was dominant in all denitrification systems, followed by Comamonas and Rhodococcus. The operational parameters described in the paper could be recommended for a full-scale wastewater treatment facility.